2021
DOI: 10.3390/ijms222111904
|View full text |Cite
|
Sign up to set email alerts
|

Association between Equol Production Status and Nonalcoholic Steatohepatitis

Abstract: Equol is a metabolite of daidzein, a major soybean isoflavone with estrogenic and antioxidant activities. As the production of equol depends on the presence of certain members of the intestinal microflora, not all individuals can produce equol. We examined the relationship between NASH histological features and equol production. In an animal model, obese OLETF rats were intraperitoneally injected with a porcine serum to augment liver fibrogenesis. Equol-rich soy product, SE5-OH was orally administered during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Three studies previously reported the association between equol production and NAFLD 14,18,19 . Two studies did not find a significant association between equol and NAFLD 18,19 .…”
Section: Discussionmentioning
confidence: 94%
“…Three studies previously reported the association between equol production and NAFLD 14,18,19 . Two studies did not find a significant association between equol and NAFLD 18,19 .…”
Section: Discussionmentioning
confidence: 94%
“… 89 In fact, like 17β-estradiol, phytoestrogens have been shown to decrease nonalcoholic fatty liver disease, 97 which was associated in one study with equol production status. 98 From in vitro and clinical studies, equol has similar actions to 17β-estradiol by stimulating collagen, elastin and TIMP expression, while inhibiting elastase and MMPs. 10 , 13 , 91 , 99 …”
Section: Update and Revision Of Information On Estrogenic Skin Treatm...mentioning
confidence: 99%
“…89 In fact, like 17β-estradiol, phytoestrogens have been shown to decrease nonalcoholic fatty liver disease, 97 which was associated in one study with equol production status. 98 From in vitro and clinical studies, equol has similar actions to 17β-estradiol by stimulating collagen, elastin and TIMP expression, while inhibiting elastase and MMPs. 10,13,91,99 For example, in a randomized, single-center 12-week clinical study women that applied a topical equol treatment twice per day displayed significant increases (across eight skin parameters) over baseline values (Figure 5).…”
Section: Update and Revision Of Information On Estrogenic Skin Treatm...mentioning
confidence: 99%
“…Akahane et al [ 50 ] recently reported that progression of NAFLD and NASH was strongly associated with the production of equol. A clinical study conducted in 38 NAFLD patients (13 men and 25 women) showed that the degree of hepatic fibrosis and ballooning was markedly higher in the equol non-producers than in the producers in women.…”
Section: Introductionmentioning
confidence: 99%
“…However, these associations were not observed in men. Limitations of the study include small sample size, a single-center study, unknown exact amounts of soy products consumed, liver fibrosis assessed by less ideal method, and inconclusive causal relationship [ 50 ]. The sex-dependent effect of equol may be attributed to the difference in the endogenous estrogen levels, abundance of hepatic estrogen receptor (ER) [ 51 ] and responsiveness to equol between males and females.…”
Section: Introductionmentioning
confidence: 99%